Design of Smart Garden Sprinklers Based on Fuzzy Logic - FADHILLAH AZMI; Jeffrey Louise; Zurfahri Rizki Sitompul; Sahsi Kumar; Jaya Surya (Universitas Medan Area, 2020)
Human needs for the existence of an automatic equipment that controls every activity becomes a necessity at this time, one of which is on watering plants that are still done manually. Treatment of plants is not optimal. Sometimes plants forget to be watered, so the plants wither quickly because of lack of water. And often watering plants over and over again, ignoring that too much water content in the soil, which causes plants to rot easily. With this controller can be applied to various fields such as home, plantation, and agriculture. The application of automatic watering control can be overcome if there is excess water capacity, here is an alarm as a warning when the weather is rainy, by using a soil moisture sensor to detect water levels on the ground, light sensors to control the tool can only function in the morning and afternoon because if at night watering plants is not good for plant growth that is controlled on an arduino microcontroller, and uses a fuzzy logic method to determine the process parameters of sensor control. The results of testing the tools carried out periodically testing can work in sync based on the parameters applied using the fuzzy logic method.Keywords: Smart garden, sprinklers, fuzzy logic.